2010
DOI: 10.1136/jnnp.2009.187633
|View full text |Cite
|
Sign up to set email alerts
|

Segmental innervation in lumbosacral transitional vertebrae (LSTV): a comparative clinical and intraoperative EMG study

Abstract: Intraoperative EMG monitoring of surgically decompressed nerve roots was found to be the ideal means of unequivocal determination of segmental innervation in LSTV patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 72 publications
0
10
0
2
Order By: Relevance
“…It was felt that the lumbar plexus was more at risk of injury at the lower levels of the lumbar spine and that the use of a Jackson table that allows for lateral flexion could help open the operative window. 1,15,16 Our patient's pathology involved multiple areas of degeneration requiring interbody fusion from L2 to S1 to correct the deformity. The disc height space had also become narrowed significantly at L4-L5 and L5-S1, requiring reconstruction of appropriate vertebral spacing and restoration of the normal vertebral alignment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was felt that the lumbar plexus was more at risk of injury at the lower levels of the lumbar spine and that the use of a Jackson table that allows for lateral flexion could help open the operative window. 1,15,16 Our patient's pathology involved multiple areas of degeneration requiring interbody fusion from L2 to S1 to correct the deformity. The disc height space had also become narrowed significantly at L4-L5 and L5-S1, requiring reconstruction of appropriate vertebral spacing and restoration of the normal vertebral alignment.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the possibility of operative repair at inappropriate levels due to mislabeling, care must be taken during any lumbar spine surgery in patients with an LSTV to appropriately localize the target level. 16,17 A pre-operative MRI that images the thoracic and lumbar spine should be obtained to avoid any confusion that may be created if only local lumbar views are obtained. 18 An in-depth clinical exam with appropriate pre-operative imaging should be combined with intra-operative monitoring and fluoroscopy to ensure that the appropriate level is identified and the correct procedure is performed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the root emerging from L6/S not only primarily resembles the S1 root but also shows characteristics of the S2 nerve, with a tendency to innervate the biceps femoris muscle. 25 Seyfert, with careful use of cremasteric reflex, concluded that lumbarization shows a dermatome gap between the lumbar dermatomes C1-C3 and the sacral dermatomes S2 and S3, which lay significantly more ventral than in patients with a normal spinal configuration. 26 The alteration in nerve root innervation caused by a transitional vertebra may make it difficult to find the pain generator.…”
Section: Anatomical Variationsmentioning
confidence: 99%
“…Çoğu yazar LSTV'nin en iyi anteroposterior (AP) grafilerde görülebileceğini kabul etmiştir. Ancak bazıları tartışmaları daha ileriye gö-türerek, kraniale doğru 30 derece açıyla çekilen ferguson grafilerini savunmuşlardır (1,(3)(4)(5)(6) . Bu çalışmada, son kostaların vertebral gövde ile olan ekleminin, tüm lomber vertebra transvers proseslerin ve sakral kanadın tümünün net olarak göründüğü çeşitli nedenlerle çekilen abdominal grafiler incelendi.…”
Section: Introductionunclassified